Phylogenetic analysis reveals positive correlations between adaptations to diverse hosts in a group of pathogen-like herbivores. (1st October 2015) - Peterson, Daniel A.; Hardy, Nate B.; Morse, Geoffrey E.; Stocks, Ian C.; Okusu, Akiko; Normark, Benjamin B.
Abstract: A jack of all trades can be master of none—this intuitive idea underlies most theoretical models of host-use evolution in plant-feeding insects, yet empirical support for trade-offs in performance on distinct host plants is weak. Trade-offs may influence the long-term evolution of host use while being difficult to detect in extant populations, but host-use evolution may also be driven by adaptations for generalism. Here we used host-use data from insect collection records to parameterize a phylogenetic model of host-use evolution in armored scale insects, a large family of plant-feeding insects with a simple, pathogen-like life history. We found that a model incorporating positive correlations between evolutionary changes in host performance best fit the observed patterns of diaspidid presence and absence on nearly all focal host taxa, suggesting that adaptations to particular hosts also enhance performance on other hosts. In contrast to the widely invoked trade-off model, we advocate a "toolbox" model of host-use evolution in which armored scale insects accumulate a set of independent genetic tools, each of which is under selection for a single function but may be useful on multiple hosts.